Exploring the Siderophore Portfolio for Mass Spectrometry-Based Diagnosis of Scedosporiosis and Lomentosporiosis - Houšt', Jiří; Palyzová, Andrea; Pluháček, Tomáš; Novák, Jiří; Marešová, Helena; Hubáček, Petr; Dobiáš, Radim; Stevens, David A; Guegan, Hélène; Gangneux, Jean-Pierre; Havlíček, Vladimír (ACS omega, 2024)
Scedosporium apiospermum and Lomentospora prolificans secrete siderophores (iron scavengers) during hyphal proliferation. Siderophores are virulence factors and potential clinical biomarkers of invasive scedosporiosis and lomentosporiosis. Both strains secreted a uniform spectrum of siderophores, including coprogen B (CopB), N α-methyl-coprogen B, dimethyl-coprogen, and ferricrocin, with N α-methyl-coprogen B being the fastest secreted and most abundant coprogen. Under iron and zinc restriction, reflecting a nutrient-limited host environment, L. prolificans secreted 45 times more CopB than did S. apiospermum, presumably contributing to its higher virulence. This robust mobilization of CopB was further enhanced by zinc surplus. Additionally, two novel cyclic peptides, Scedocyclin A and B, were characterized inScedosporium boydii using the de novo sequencing tool CycloBranch. Utilizing matrix-assisted laser desorption/ionization, the portfolio of coprogens detected had limits of detection and quantitation of 4.9 and 14.6 fmol/spot in complex matrices, respectively, making them strong candidates for the next-generation, routine diagnosis of invasive scedosporiosis and lomentosporiosis through the Biotyper siderotyping.